Biphasic MoO2/Mo2C-Passivated Graphite Anodes for Fast-Charging Lithium-Ion Batteries - Bae, Sang Hyeok; Suh, Joo Hyeong; Jo, Yejin; Cho, Yong Jun; Cho, Min Kyung; Park, Jung Hwan; Park, Min-Sik; Jeong, Sunho (American Chemical Society, 2025)
Fast charging of commercial lithium-ion batteries severely compromises long-term cycle durability, particularly in cells using high mass-loading thick electrodes. Such performance decay originates from interfacial kinetic limitations in the graphite anode as follows: (i) a sluggish Li+ desolvation at the electrolyte–graphite interface, (ii) a hindered Li+ diffusion across the solid electrolyte interphase (SEI), and (iii) a restricted Li+ insertion into the graphite, which collectively lead to an undesirable Li plating. Herein, we introduce an ultrathin and uniform MoO2/Mo2C biphasic passivation layer, achieved through a sequential cationic polyelectrolyte-assisted molybdate adsorption approach. The outer MoO2 layer does not only suppress an excessive SEI formation but also stabilizes the electrolyte interface by promoting the formation of Li2O and LiF-rich SEI that are both ionically conductive and chemically robust. The inner Mo2C layer provides a low Li+ adsorption energy (−0.97 eV), a reduced surface diffusion barrier (43 meV), and a high electrical conductivity (∼104 S cm–1), consequently enabling capacitive behavior and fast intercalation kinetics at the edge plane. The biphasic layer-passivated graphite anode delivers a fast-charging capability, reaching the 80% state of charge in just 7.4 min at a current density of 6 C and retaining 78.3% of its initial capacity after 600 fast-charge cycles with a practically viable high areal capacity of 3.2 mAh cm–2. These results represent a notable advancement over previously reported surface-engineered graphite anodes, particularly under industrially demanding conditions including high mass-loading and fast-charging.